Influence of geographical origin, harvesting time and processing system on the characteristics of olive-mill wastewater: A step toward reducing the environmental impact of the olive oil sector - Aline Issa (11935946) (2023)
The olive oil production sector generates considerable quantities of liquid by-products (olive-mill wastewater, OMWW) which, if left untreated, can cause detrimental environmental impacts. This study aimed to investigate the influence of the Lebanese geographical origin, harvesting time and processing system and their interactions on the chemical and biological characteristics of these by-products. The results showed that the interaction of all the three studied factors on the chemical composition of OMWW, were highly significant (p < 0.001). Furthermore, all the OMWW could be considered as a rich source of natural phenolic and antioxidant compounds. The average Total Phenolic Content in OMWW samples was 807.56 GAE/ kg with significantly higher values for OMWW obtained from the North (1027.7 GAE/ kg) at early harvest (1024.00 GAE/ kg) and using press system (1036.13 GAE/ kg) as compared to the other samples from the South, intermediate and late harvesting time using 3-phases and Sinolea (p < 0.05). The overall results of this study shed light on the need to establish a sustainable means of treating the liquid effluents of olive mills. The results can help prioritize the regions in most need for a treatment system based on the values reported, while redirecting our attention to the possibility of valorizing the phenolic contents as potent raw material rather than pollutants, in an aim to enhance sustainable agriculture and help achieve (sustainable development goal) SDG6 for improved water quality by 2030. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eti.2023.103365